Enhancing Performance and Worker Satisfaction at Tokonekoncoku Logistics Warehouse through Ergonomic Interior Design: A DMADV and CTQ-Based Study - Rachmanto, Danny Dwi; Novelia, Adinda Sukma; Puspita, Feni Ira; Ardianto, Rizal; Fatimah, Siti (TALENTA Publisher, 2025)
The rapid expansion of the e-commerce sector has imposed considerable demands on Usaha Mikro, Kecil, dan Menengah (UMKM) to enhance the operational efficiency of their logistics warehouses. This study aims to improve organizational performance and employee well-being at Tokonekoncoku, a logistics UMKM, through an ergonomic workplace redesign. The research employs the Define, Measure, Analyze, Design, Verify (DMADV) methodology, emphasizing Critical to Quality (CTQ) parameters to ensure that the proposed interventions are both contextually relevant and quantitatively measurable. The CTQ priorities identified include operational time efficiency, productivity enhancement, and workforce satisfaction. By systematically implementing ergonomic principles—encompassing layout reorganization and workstation modifications—the study demonstrates a significant improvement in the efficiency and comfort of the work environment. The findings underscore that the integration of ergonomic design within the DMADV framework offers a robust approach to simultaneously advancing operational performance and promoting worker well-being in UMKM logistics settings.